Multiple sclerosis in the Republic of San Marino. Issue 1 (March 1984) - Morganti, G; Naccarato, S; Elian, M; Ferrari, P; Kelly, R; Karhausen, L; Dean, G
Abstract : Previous studies on the prevalence of multiple sclerosis in Italy have grossly underestimated the prevalence of the disease. The prevalence in the Republic of San Marino (near Rimini), in Sicily, and no doubt in the rest of Italy, is of the same order of magnitude as in Europe–that is, 40-60/100 000. The contrast of this with the very low prevalence in Malta (only 60 miles (96 km) away from Sicily) of 4/100 000 should provide a clue to the genetic and environmental factors responsible for multiple sclerosis.